Rebranding strategies and visual identity design for Chinese online casual menswear brands - Jundi, Dai (2025)
The Chinese online casual menswear market is experiencing critical challenges, including visual homogenization, a lack of culturally resonant identity, and limited strategic frameworks for rebranding. This research investigates how visual identity design—particularly through the lens of super symbols—can enhance brand distinctiveness and consumer engagement in this highly saturated sector. The study aims to analyse the visual characteristics of Chinese online casual menswear brands, identify key elements of effective branding, explore the role of super symbols, and develop a strategic model for visual rebranding. A qualitative research approach was adopted, involving in-depth interviews with 19 purposively selected industry experts and practitioners. The data were thematically analysed using NVivo to ensure analytical rigour and reliability. Results reveal that many Chinese brands continue to rely on Western visual aesthetics while neglecting their own cultural symbolism, leading to weak brand narratives and low consumer recall. The study identifies colour schemes, typography, and logos as core components of visual identity that can be transformed through the integration of culturally meaningful super symbols. The research contributes theoretically by expanding existing branding literature to include the underexplored concept of super symbols in the context of Chinese digital fashion. Practically, it offers a rebranding framework that integrates cultural symbolism and strategic design, providing actionable insights for brand practitioners. The study finds that super symbols enhance brand differentiation and consumer engagement in Chinese fashion branding, strengthening emotional connections and long-term loyalty. The final outcome is a strategic visual rebranding model tailored to the needs of Chinese online casual menswear brands, offering guidance on how to embed culture-driven super symbols into brand design. This research addresses critical industry gaps and lays a foundation for future studies across other fashion segments and regional markets.